Prologue. La littérature : arme bouclier et canon - Richard , Élisabeth (Neofilolog, 2022)
If literature crosses the ages, the sudden irruption of a socio-political context of war makes certain texts particularly resonant and exposes the vital necessity of literature to transcend the trials of time.